2017
DOI: 10.1021/acs.joc.7b00436
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Transfer Hydrogenation of (Hetero)arylketones with Tethered Rh(III)–N-(p-Tolylsulfonyl)-1,2-diphenylethylene-1,2-diamine Complexes: Scope and Limitations

Abstract: A series of new tethered Rh(III)/Cp* complexes containing the N-(p-tolylsulfonyl)-1,2-diphenylethylene-1,2-diamine ligand have been prepared, characterized, and evaluated in the asymmetric transfer hydrogenation (ATH) of a wide range of (hetero)aryl ketones. The reaction was performed under mild conditions with the formic acid/triethylamine (5:2) system as the hydrogen source and provided enantiomerically enriched alcohols with good yields and high to excellent enantioselectivities. Although the nature of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(23 citation statements)
references
References 72 publications
(78 reference statements)
0
23
0
Order By: Relevance
“…193 In conjunction with a base (such as Et3N) or as sodium formate, formic acid has been widely used as a reducing agent, decomposing into CO2 and H2 under catalytic conditions. 194 It has been particularly useful in prochiral ketone reduction into secondary alcohol, using Ir, 195 Ru, [196][197][198] Rh complexes, 199 or enzymes 200 (Scheme 18A). Furthermore, LA is co-generated with LA 5-HMF acidolysis, 17 giving a strong incentive to use FA to reduce LA.…”
Section: Formatementioning
confidence: 99%
“…193 In conjunction with a base (such as Et3N) or as sodium formate, formic acid has been widely used as a reducing agent, decomposing into CO2 and H2 under catalytic conditions. 194 It has been particularly useful in prochiral ketone reduction into secondary alcohol, using Ir, 195 Ru, [196][197][198] Rh complexes, 199 or enzymes 200 (Scheme 18A). Furthermore, LA is co-generated with LA 5-HMF acidolysis, 17 giving a strong incentive to use FA to reduce LA.…”
Section: Formatementioning
confidence: 99%
“…To obtain the anti-isomer of fragment B, we turned our attention to the use of asymmetric transfer hydrogenation of 17 in combination with dynamic kinetic resolution. Preliminary screening employing different catalysts Cat I, 41 Cat II, 42 and Cat III 43,44 with HCOOH/Et3N (5:2) as the hydrogen donor demonstrated that faster reaction times as well as better diastereoselectivities in favor of compound anti-23 (dr = 78:22) were obtained with catalyst Cat III. Moreover, the catalytic charge could be decreased from 2 mol% to 0.1 mol% without any loss of stereoselectivity and compound 23 was isolated with a comparable 70% yield.…”
Section: Synthesis Of Fragment Bmentioning
confidence: 99%
“…[30][31][32][33][34][35] Indeed, stereoselective ATH of 1-indanones or 2-substituted-1indanones to produce corresponding 1-indanols or 2substituted-1-indanols, which utilize chiral transition metal (Ru, Rh) catalysts and a HCO 2 H/Et 3 N mixture as a hydrogen source, have already been described. [36][37][38] However, no examples have been reported thus far of ATH promoted transformations of 3-aryl-1-indanones to 3-aryl-indanols having stereogenic centers at C-3. This deciency encouraged us to explore the stereochemical outcome of ATH reactions of 3-aryl-indanones using enantioenriched chiral transition metal catalysts and a HCO 2 H/Et 3 N mixture as the hydrogen source.…”
Section: Introductionmentioning
confidence: 99%